Austronautic Registers: Translation Strategies and Acceptability - Hakim, Azhar L; Kholifah, Asrofin Nur; Purwaningsih, Dyah R (Jurnal Bahasa, Sastra, dan Studi Amerika, 2024)
This study aims to investigate the translation strategies to translate the astronautic registers as well as the acceptability aspect of the translation. The data comprise 74 astronautic registers in the source text and translated version of The Martian novel. A questionnaire with inputs from the respondents is also put into consideration. The results show that 6 translation strategies consist of translation by a more general word (12%), translation by a more neutral or less expressive word (22%), translation by loan word and loan word plus explanation (17%), translation by paraphrase using related words (31%), translation by paraphrase using unrelated words (15%), translation by omission (3%). This implied most of the registers actually has a similar equivalent in the TL, but the form has to be modified in the TL to capture the main message. Furthermore, in terms of acceptability, 58% data are acceptable, 35% data are less acceptable, and 7% data are unacceptable. It indicates there are still a high number of translations that fail to capture the intended meaning of the registers, bear no nuance as a technical term, and sound unnatural in the TL.